A Humanistic Pesantren Curriculum Model Based On Digital Technology For Strengthening 21st-Century Competencies - Arizqi, Arizqi Ihsan Pratama; Fauzi, Anas; Muhammad, Muhd Rosydi (LPPM Universitas Ibn Khaldun, Bogor, 2026)
This study explores the integration of digital technologies into the development of a humanistic pesantren curriculum aimed at strengthening 21st-century competencies. The primary objective is to examine how digital tools can enhance the learning experience in pesantren while preserving Islamic educational values. The research follows a Systematic Literature Review (SLR) approach, utilizing frameworks like Social Cognitive Theory, Technology Acceptance Model (TAM), and Institutional Theory to analyze existing studies from Southeast Asia, particularly Indonesia, and global perspectives on digital integration in Islamic education. The methodology involves synthesizing findings from a wide range of quantitative and qualitative studies, focusing on the challenges and benefits of digital technology in religious educational settings. The analysis identifies key themes such as digital leadership, technology adoption, and the integration of 21st-century skills like creativity, critical thinking, and collaboration. Notably, the findings reveal that while digital tools have enhanced engagement and academic outcomes, there remains a significant gap in understanding their long-term impact on students' religious identity and moral development. The integration of technology must align with Islamic values to ensure that it complements, rather than undermines, the core principles of religious education. This review offers a novel perspective by proposing a holistic curriculum model that balances technology with religious teachings. Future research should focus on longitudinal studies to assess the long-term impact of technology on students' spiritual growth, as well as develop context-specific theoretical frameworks that address the unique challenges of digital integration in Islamic education. The findings underscore the importance of culturally grounded curriculum and policy development for sustainable digital transformation in Islamic education.